Low cost solar tracker - Marliyani, Omar (2009)
Photovoltaic, or PV for short, is a technology in which light is converted into electrical power. One of the applications of PV is in solar tracker. A solar tracker is a device for operating a solar photovoltaic panel or concentrating solar reflector or lens forward sun-concentrates, especially in solar cell application, require high degree of accuracy to ensure that the concentrated sunlight is dedicated precisely to the power device. Solar tracker is invented because solar panel disables to move toward the sunlight when the sun moves from east to west. In order to produce maximum power output, solar tracker is design with motor so that the solar panel will move toward the position of sun. To control the solar panel so that it will always face the sun, the circuit has timer that consistent to the sun movement. The timer indicates the time to move solar panel in 12 hours. It moves the solar panel every one hour. It gives signal to the motor to move the solar panel. When the solar panel face directly to the sun and has maximum concentrated sunlight to the solar panel, the maximum power output will produce. The solar tracker is design as active tracker. It moves according to the sun movement and controlled by microcontroller. The solar tracker is design as low cost and easily to use. The solar tracker is design low cost due to the expensive of solar panel. To make sure to have enough demand electricity, we use more photovoltaic module. To decrease the cost, we use solar tracker. Besides that, this solar tracker use to save electricity in producing maximum power from solar panel because solar power is renewable energy